UNDERSTANDING RELIGION-STATE RELATIONS IN MUSLIM SOCIETIES: Beyond Essentialist and Secular-Liberal Narratives - Abdi, Supriyanto (Universitas Islam Indonesia, 2017)
Scholars have offered different accounts in the debates over religion-state relations in the Muslim world. Central to their differing views are diverging premises on the degree to which religion-state relations in Muslim societies are dictated or determined by certain ‘essential’ cultural, religious or even civilizational characteristics. Another main root of conflicting analyses is different assumptions on the extent to which the discourse of religion-state relations should be confined to their distinctively secular-liberal character. While some discuss religion-state relations within strictly secular-liberal terms, others choose to go beyond these particular narratives. This paper revisits the debate on religion-state relations in the Muslim world in light of these two main roots of contention. The chapter begins with a critical examination of the cultural essentialist approach and its limited analytical value in the discussion on religion-state relations in the Muslim world. It then examines the dominant secular-liberal narratives of state-religion and their problematic projection within the context of Muslim societies. Finally, it offers an overview of the internal debate within the Muslim world over the issue of religion-state relations, focusing more specifically on the extent to which secular liberal discourses are contested or critically embraced. Keywords: Religion-state Relations, Secular-liberal Narratives, Muslim Societies